Problem of Determining Past Income for Children in Court the Decisions - Lisa, Masnuah (PT. Riset Press International, 2023)
The data obtained were then analyzed using the content analysis method. Decision Religious shows that the legal basis for refusing claims for māḍiyah maintenance for children in divorce is legal considerations as considered by the Supreme Court in its decision rejecting lawsuits for past maintenance for children, namely that the father's obligation to provide for his child is lil-intifā’, not lit -tamlīk, then a person's negligence fathers who do not provide for their children cannot be sued. This leads to injustice because māḍiyah maintenance is not granted to children. This will certainly be detrimental to the life and welfare of the child, who in other circumstances can become a shield for a father who neglects to provide for his child. Māḍiyah's livelihood is a form of protection for the rights of divorced women and children born during a marriage. This is in line with the verses of the Koran and hadith which talk about the obligation of a father to his wife and children to provide maintenance.